Relationships between lower body muscle structure and isometric mid-thigh pull peak force - McMahon, J. J.; Stapley, J. T.; Suchomel, T. J.; Comfort, P. (Journal of Trainology, 2015)
Objectives: To explore relationships between aspects of vastus lateralis (VL) and medial gastrocnemius (MG) muscle structure (muscle thickness, fascicle length and pennation angle) and isometric mid-thigh pull (IMTP) peak force capacity. Design and Methods: Fifteen male collegiate athletes (height 1.79 ± 0.05 m; body mass 82.8 ± 8.1 kg, age 23.2 ± 3.4 years), from a wide range of field-based sports, had sonographic images of their VL and MG musculature (for the dominant leg) recorded at rest before participating in a standardized maximal IMTP protocol. Results: Intraclass correlation coefficients (= 0.91, p < 0.001) and coefficient of variation percentages (= 2.5%) showed excellent reliability of the muscle structure and IMTP peak force measurements. A large positive relationship was found between VL muscle thickness and absolute IMTP peak force (r = 0.62, p < 0.01, power = 0.89). Moderate, but non-significant, relationships were observed between VL pennation angle and both absolute (r = 0.41, p = 0.06, power = 0.60) and relative (r = 0.39, p = 0.08, power = 0.46) IMTP peak force. A small non-significant correlation was noted between VL muscle thickness and relative IMTP peak force (r = 0.26, p = 0.19). No aspect of MG muscle structure was significantly correlated with IMTP peak force. Conclusion: The VL muscle thickness of male collegiate athletes` dominant leg is largely correlated to their bilateral absolute IMTP peak force capacity (demonstrating 38% shared variance). Practitioners should, therefore, develop hypertrophy of male collegiate athletes` VL musculature through appropriately designed strength training programs.